Real-Time Multitasking Kernel For IBM-Based Microcomputers - Samaka, Mohammed (Malaysian Journal of Computer Science, 2017)
Presents a real-time multitasking kernel (RTMK) for the IBM-based computers. It is developed using the Modula-2 Top Speed version. RTMK offers an expanded set of synchronisation and communication primitives that are dynamically created, and included with a time-out control mechanism. The kernel provides a base around which realtime application systems can be built. Its flexible and modular design simplifies the expansion of the kernel.